2017
DOI: 10.5194/isprs-annals-iv-4-w5-1-2017
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Integration of Gis and Bim Data: What Are the Geometric And Topological Issues?

Abstract: ABSTRACT:Geographic information and building information modelling both model buildings and infrastructure, but the way in which they are modelled is usually complimentary and BIM-GIS integration is widely considered as a way forward for both domains. For one, more detailed BIM data can feed more general GIS data and GIS data can provide the context that is necessary to BIM data. While previous studies have focused on the theoretical aspects of such an integration at a schema level, in this paper we focus on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…Additional key publications in terms of BIM/GIS integration include Deng, Cheng, and Anumba (2016), Wang, Krijnen, and de Vries (2016), Arroyo Ohori et al (2017), Ohori, Diakité, Krijnen, Ledoux, and Stoter (2018), and Stouffs, Tauscher, and Biljecki (2018). Additionally, BIM to GIS conceptual mapping (B2GM) is currently being standardized by ISO (2019).…”
Section: Possible Bim/gis Integration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional key publications in terms of BIM/GIS integration include Deng, Cheng, and Anumba (2016), Wang, Krijnen, and de Vries (2016), Arroyo Ohori et al (2017), Ohori, Diakité, Krijnen, Ledoux, and Stoter (2018), and Stouffs, Tauscher, and Biljecki (2018). Additionally, BIM to GIS conceptual mapping (B2GM) is currently being standardized by ISO (2019).…”
Section: Possible Bim/gis Integration Methodsmentioning
confidence: 99%
“…To carry out BIM/GIS integration, Amirebrahimi, Rajabifard, Mendis, and Ngo () and Liu et al () identified three levels of integration: (1) integration at data level (through linking, translation/conversion, extension and meta‐models/mediation); (2) integration at process level (integration through semantic web technologies or service‐based methods); and (3) integration at application level (integration through reconfiguring or rebuilding). At data level, Liu et al () estimate that the “EEEF” (effectiveness, extensibility, effort, and flexibility) of using new standards and models “highly depends on their ambitions,” but “if the new model aims to solve one particular small and focused problem, […it] can be very satisfying.” They further state that the EEEF of conversion, translation, and extension of existing standards depends on whether it is accomplished in a semi‐automatic way or in a manual way, but both “involve semantic filtering (ignoring or mapping) process,” which usually results in a “certain level of information loss.” Additional key publications in terms of BIM/GIS integration include Deng, Cheng, and Anumba (), Wang, Krijnen, and de Vries (), Arroyo Ohori et al (), Ohori, Diakité, Krijnen, Ledoux, and Stoter (), and Stouffs, Tauscher, and Biljecki (). Additionally, BIM to GIS conceptual mapping (B2GM) is currently being standardized by ISO ().…”
Section: State Of the Artmentioning
confidence: 99%
“…Currently, the combination of GIS and BIM technologies has become a trend that has great demand. This combination is widely regarded as a major research direction to break through the bottlenecks in current research areas, such as urban management, environmental planning, and emergency management [8][9][10][11][12][13]. This paper also starts from this basis and proposes a new urban management method to meet these needs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently the Industry Foundation Classes (IFC) format is used as an open standard format for the BIM objects. According to (Ohori et al, 2017), most IFC objects are built by integrating sweep volumes, explicit faceted surface models and Constructive Solid Geometry (CSG).…”
Section: Introductionmentioning
confidence: 99%